Efeito do fator de crescimento epidermal (EGF) na maturação in vitro de oócitos caninos - Pereira, Leda Maria Costa [UNESP]; Bersano, Paulo Ricardo de Oliveira; Lopes, Maria Denise [UNESP] (My University, 2014)
This work aimed to evaluate the influence of EGF on canine oocyte in vitro maturation (IVM). We carried out the transport of the ovaries in sodium chloride 0.9% solution, which were cut into phosphate-buffered saline (PBS) and the cumulus oocyte complexes (COCs) selected in tissue culture medium (TCM), supplemented with 199 HEPES. A total of 405 grade 1 oocytes were collected from bitches in anestrus and diestrus. Oocytes from the two phases of estrous cycle were subjected to two treatments: medium with addition of 10 ηg/mL epidermal growth factor (EGF) (T) and medium without supplementation (C). After 72 h of maturation, COCs were denuded, fixed and stained with Hoechst 33342 to assess nuclear maturation. The oocytes obtained from the ovaries of the diestrus phase of the T group demonstrated higher percentage (18.8%) of oocytes at metaphase II stage (M-II) than C group (1.3%) (p < 0.01). The oocytes from anestrus phase demonstrated difference (p < 0.05) between the groups, observing smaller proportion (4.1%) of oocytes at the stage of germinal vesicle (GV) in group T compared to group C (16.1%). Comparing the different reproductive status in media supplemented with EGF difference (p < 0.05) was observed only in oocytes diestrus phase relative to the stage of M-II. Thus, supplementation on maturation medium at a concentration of 10 ηg/mL of EGF in this study had positive influence only on IVM of canine oocytes obtained from diestrus phase, increasing the levels of M-II in this species.
Effect of epidermal growth factor (EGF) on in vitro maturation of canine oocyte
Keywords: Anestrus; Bitch; Diestrus; EGF; In vitro maturation